Progressive Decrease in Coronary Vascular Function Associated With Type 2 Diabetic Heart Disease - Katare, Rajesh; Pearson, James T.; Lew, Jason Kar-Sheng; Wei, Melanie; Tsuchimouchi, Hirotsugu; Du, Cheng-Kun; Zhan, Dong-Yun; Umetani, Keiji; Shirai, Mikiyasu; Schwenke, Daryl O. (Frontiers in Physiology, 2018)
Background: The causal factors underpinning the onset and progression of diabetic heart disease (DHD) remain to be fully elucidated. Myocardial function is critically dependent on optimal coronary blood flow. Considering vascular disease occurs early in diabetes due to endothelial dysfunction, this study aimed to determine whether impaired coronary perfusion contributes to the origins of myocardial dysfunction in DHD, or whether coronary and cardiac dysfunction are independent pathologies associated with diabetes. Methods: Synchrotron radiation microangiography was used to image the coronary circulation of type-2 diabetic db/db and non-diabetic db/+ mice in vivo at 8, 16 and 24 weeks of age. We further assessed vascular function based on the vasodilatory responses to acetylcholine (ACh, 3 µg/kg/min), sodium nitroprusside (SNP, 5 µg/kg/min) and the Rho-kinase inhibitor, fasudil (20 mg/kg, i.v.). Cardiac function was assessed using echocardiography, and cardiac eNOS and ROCK expression were measured using immunohistochemistry. Results: Coronary and cardiac function were normal in 8 week old diabetic mice. However, by 16 weeks of age, diabetic mice had advanced cardiac dysfunction. In comparison, normal coronary perfusion was preserved in diabetes until 24 weeks of age. Moreover, only the 24-week old diabetic mice showed clear evidence of advanced coronary vascular dysfunction, based on i) the absence of a vasodilatory response to ACh, and ii) an exaggerated vasodilatory response to fasudil. Interestingly, fasudil also restored normal coronary perfusion in the 24-week old diabetic heart by restoring blood flow to previously-constricted vessels (diameter <100 µm). Importantly, there was a ubiquitous decrease, and increase, in the cardiac expression of eNOS and ROCK, respectively. Conclusion: These results suggest that both cardiac and coronary dysfunction appear to have independent origins associated with diabetes and Rho-kinase pathway may be playing a role in the onset and progression of DHD.